Exonic mutations of POU class 1 homeobox 1 are associated with milk pH in high-producing Holstein Friesian cows - Muhammad Cahyadi; Ammar Ibnu Hasan; Djorodjatun Samodro Sakti; Nasta ‘Ainun Nissa; Ahmad Pramono; Suryo Firmanto; Rizwan Nur Friyatna; Slamet Diah Volkandari; Pita Sudrajad (Veterinary World)
Background and Aim: Milk physicochemical properties play essential role in the milk processing industry, which are moderately to highly affected by genetic factors. This study aimed to evaluate the association between single nucleotide polymorphisms in POU class 1 homeobox 1 (POU1F1) and the physicochemical properties of milk in high-producing Holstein Friesian (HF) cows.